Devising technologies for harvesting hemp with belt threshers - Sheichenko, Viktor; Shevchuk, Vitaliy; Dudnikov, Igor; Koropchenko, Serhii; Dnes, Viktor; Skoriak, Yuliia; Skibchyk, Volodymyr (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports the system of devised technologies for harvesting hemp with belt hemp threshers. It is proposed to form a roll of mowed hemp stems on a belt and tramp it to the field edge for further processing of stems. That makes it possible to significantly improve the efficiency of mechanized processes when harvesting and processing the entire biological harvest of hemp. Thus, the level of handling hemp production systems has been increased. At the same time, the management of the process of roll formation of hemp stems has been improved. The technology of hemp harvesting has been improved with the possibility of obtaining raw materials for long fiber and therapeutic preparations. Two-phase harvesting (for seeds and fiber) has been proposed to be implemented by using belt hemp threshers included in the stationary (semi-stationary) complexes. The possibility of preparing the combed hemp retted stalks by spreading them on materials of various types has been systematically substantiated. The influence of the thickness of a layer of hemp stalks spread out for the preparation of retted stalks on the timing of their preparation and fiber quality indicators has been investigated. It was established that in terms of the quality indicators of the produced fiber, the retted stalks from all experiments are properly aged while the efficiency of their processing for medium- and large-stalk fraction is high. The fibers produced in all experiments were characterized by purity, as well as high indicators of breaking load and handful length. As regards the linear density, the fibers’ values in all experimental variants exceeded the normative ones by 1.65‒2.64 times, which rendered them non-standard. An increase in the values of quality indicators has been established with the corresponding change, from 1 to 3 kilograms per meter, in the thickness of the layer of combed hemp stalks. The breaking load, under such conditions, increased by 16.6 %; the linear density, by 20 %; the content of shives, by 60 %; the «paw» content, by 12.5 %, the content of bast strands, by 10.8 %.